Long-term evidence for ecological intensification as a pathway to sustainable agriculture - MacLaren, C.; Mead, A.; Balen, D. van; Claessens, Lieven; Etana, A.; Haan, J. de; Haagsma, W.; Jack, O.; Keller, T.; Labuschagne, J.; Myrbeck, A.; Necpalova, M.; et al. (Springer, 2022)
Ecological intensification (EI) could help return agriculture into a ‘safe operating space’ for humanity. Using a novel application of meta-analysis to data from 30 long-term experiments from Europe and Africa (comprising 25,565 yield records), we investigated how field-scale EI practices interact with each other, and with N fertilizer and tillage, in their effects on long-term crop yields. Here we confirmed that EI practices (specifically, increasing crop diversity and adding fertility crops and organic matter) have generally positive effects on the yield of staple crops. However, we show that EI practices have a largely substitutive interaction with N fertilizer, so that EI practices substantially increase yield at low N fertilizer doses but have minimal or no effect on yield at high N fertilizer doses. EI practices had comparable effects across different tillage intensities, and reducing tillage did not strongly affect yields.